Annexin A1 as a target for managing murine pristane-induced systemic lupus erythematosus. (19th May 2017) - Mihaylova, Nikolina; Bradyanova, Silviya; Chipinski, Petroslav; Herbáth, Melinda; Chausheva, Stela; Kyurkchiev, Dobroslav; Prechl, József; Tchorbanov, Andrey I.
Abstract: Systemic lupus erythematosus (SLE) is a polygenic pathological disorder which involves multiple organs. Self-specific B cells play a main role in the lupus pathogenesis by generating autoantibodies as well as by serving as important autoantigen-presenting cells. Autoreactive T lymphocytes, on the other hand, are responsible for B cell activation and proliferation, and cytokine production. Therefore, both factors promote the idea that a down-modulation of activated self-reactive T and B cells involved in the pathogenic immune response is a reasonable approach for SLE therapy. Annexin A1 (ANX A1) is expressed by many cell types and binds to phospholipids in a Ca 2+ dependent manner. Abnormal expression of ANX A1 was found on activated B and T cells in both murine and human autoimmunity, suggesting its potential role as a therapeutic target. While its role on T lymphocytes is through formyl peptide receptor-like molecules (FPRL), and the formed ANX A1/FPRL pathway modulates T cell receptor signalling, there is still no fool-proof data available for the role of ANX A1 in B cells. We employed a lupus model of Balb/c mice with pristane-induced SLE which very closely resembles human lupus. In the present study, we investigated the possibility to modulate the autoimmune response in a pristane-induced mouse model of SLE using an anti- ANX A1 antibody. Administration of this monoclonal antibody resulted in the inhibition of T-cell activation and proliferation, suppression of IgG anti-dsDNA antibody-secreting plasma cells and of proteinuria, decreased disease activity and prolonged survival compared to control group.